Cardiovascular risk factors are not present in adolescents with inflammatory bowel disease. (4th March 2020) - Dorfman, Lev; Ghersin, Itai; Khateeb, Neron; Daher, Saleh; Shamir, Raanan; Assa, Amit
Abstract: Aim: Due to conflicting data, we aimed to investigate the association of inflammatory bowel disease (IBD) with cardiovascular disease (CVD) risk factors at late adolescence in a cross‐sectional population‐based study. Methods: A total of 1 144 213 Jewish Israeli adolescents who underwent a general health examination prior to enlistment at median age of 17.1 years from 1988 to 2016 were included. Covariate data included demographics, blood pressure, resting heart rate and risk factors associated with CVD. Results: Overall, 2372 cases of IBD were identified, including 1612 cases of Crohn's disease (68%). Univariate analysis showed marginally lower systolic and diastolic blood pressure in patients with IBD with no difference following multivariate analysis. Diagnosis of Crohn's disease in males was associated with lower rates of overweight (15.8% vs 21.2%, P  < .001) and obesity (3.7% vs 6.1% P  = .003), whereas females with Crohn's disease had a lower rate of overweight (14.0% vs 17.9% P  = .04) but not obesity. Patients with ulcerative colitis did not differ from controls in terms of overweight or obesity. Patients with Crohn's disease had an increased prevalence of hereditary hypercoagulability (odds ratio 16.9, 95% confidence interval 8.0‐35.7, P  < .001). Conclusion: Significant risk factors for CVD were not present in adolescents with IBD.